Interação escola-comunidade em programas/projetos nas áreas de educação, direitos humanos e desenvolvimento social - FEO, Graziela Lionetti de (Universidade Federal do Pará, 2020)
This is paper aims to map programs / projects of federal and state governments and São Paulo city which support the implementation of interaction experiences with the school community, as envisaged in the National Plan for Human Rights Education. We surveyed the websites of the Ministry of Education, Department of Human Rights and the Departments of Education and Social Development, both from State of São Paulo including the city of São Paulo. We concluded that few programs were directly targeting the objectives of this research, since most of them indirectly apply, and some of them are designed for families and children from 0 up to 6 years old, with proposals for ensuring network social protection.